Application of Cardboard Maze Games to Improve Early Childhood Spatial Visual Intelligence - Rita Kencana (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study aims to determine the application of cardboard maze games in improving early childhood visual-spatial intelligence. Visual-spatial intelligence is important to be developed from an early age because it is related to the child's ability to understand shapes, directions, positions, spaces, and relationships between objects. Based on the literature, these abilities need to be stimulated through concrete, interactive, and interactive play activities that involve coordination of children's vision and movements. However, the results of initial observations at KB Ar-Rahman Tembilahan show that children's visual-spatial abilities have not developed optimally. This can be seen from the percentage of teacher activity of 52%, children's activity of 46%, and the results of the child's visual-spatial intelligence test of 45.55% in the pre-cycle stage. This condition shows the need for the use of interesting learning media that is in accordance with the characteristics of early childhood learning, one of which is through cardboard maze games. This study aims to determine the application of cardboard maze games in improving the visual-spatial intelligence of early childhood. The research used a mixed approach, namely qualitative and quantitative, with a type of classroom action research carried out in two cycles on 10 children aged 5–6 years at KB Ar-Rahman Tembilahan. Data were collected through observation of teacher activities, observation of children's activities, and visual-spatial intelligence tests. The results of the study showed an increase in each indicator. The percentage of learning implementation by teachers increased from 52% in the pre-cycle to 82% in the first cycle and 90% in the second cycle. Children's activity increased from 46% in the pre-cycle to 74% in the first cycle and 83% in the second cycle. The results of the children's visual-spatial intelligence test increased from 45.55% in the pre-cycle to 70% in the first cycle and 80.2% in the second cycle. These findings show that cardboard maze games effectively improve children's visual-spatial intelligence through fun, concrete, and interactive learning activities. Therefore, teachers are advised to use simple game media as one of the efforts to improve early childhood cognitive abilities.